Implication Of Farm Women In Rice Farming In Purwodadi District, Musi Rawas Regency - Vera Octalia; Nur Annisa, Febrina (Journal of Agri Socio Economics and Business, 2023)
This research aims to analyze the implications of women in rice farming in Purwodadi District, Musirawas Regency. Determining the research location using a purposive method, namely Purwodadi District, Musirawas Regency. The data sources used in this research are primary data and secondary data. This research used observation techniques, interviews, and library methods. The results of this research explain that the implications of women farming rice can be seen from the involvement of women in activities, namely seed preparation, planting, and maintenance. These results can be seen from the 100% percentage of seed preparation in the two villages, which explains how important the role of women farmers is in seed preparation activities. Furthermore, in planting activities, the percentage produced is also 100%, which highlights the important role of women farmers in rice farming. Meanwhile, in maintenance, the role of women farmers is quite important in the process of rice maintenance activities, as can be seen from the percentage results of 60–67%. Keywords: Implication, Farmer Women, Rice